PRODUCTION OF HUMAN INSULIN PRECURSOR IN A 10 LITER BIOREACTOR USING A METHANOL PULSE FEEDING - Puspitasari, Dian Japany (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Indonesia as a country that had 19.5 million diabetic patients in 2021 is still importing raw materials of human insulin. The development of human insulin production process is needed to support the government’s objective to be independent in medicine aspect. Human insulin precursor (HIP) expressed from Pichia pastoris X33/pD902-IP had been developed and optimized in small-scale cultivation. However, the scaling up in bioreactor 10 L has not been studied. Using a 10 L-bioreactor the fermentation of P. pastoris X33/pD902-IP was developed. Fermentation was done in 120 hours using a basal salt medium (half concentration) for the vegetative and induction media. To induce HIP expression, methanol is fed by pulse strategy with a gradient concentration of 1-3% (v/v) for 48 hours. The dry cell weight (DCW) and HIP titers were 72 g/L and 286 mg/L, respectively. This development is the first fermentation of HIP expressed by P. pastoris X33/pD902-IP in a 10 L-bioreactor.